Picosecond to millisecond tracking of a photocatalytic decarboxylation reaction provides direct mechanistic insights - Bhattacherjee, Aditi; Sneha, Mahima; Lewis-Borrell, Luke; Tau, Omri; Clark, Ian P.; Orr-Ewing, Andrew J. (Nature communications, 2019)
The photochemical decarboxylation of carboxylic acids is a versatile route to free radical intermediates for chemical synthesis. However, the sequential nature of this multi-step reaction renders the mechanism challenging to probe. Here, we employ a 100 kHz mid-infrared probe in a transient absorption spectroscopy experiment to track the decarboxylation of cyclohexanecarboxylic acid in acetonitrile-d 3 over picosecond to millisecond timescales using a photooxidant pair (phenanthrene and 1,4-dicyanobenzene). Selective excitation of phenanthrene at 256 nm enables a diffusion-limited photoinduced electron transfer to 1,4-dicyanobenzene. A measured time offset in the rise of the CO 2 byproduct reports on the lifetime (520 ± 120 ns) of a reactive carboxyl radical in solution, and spectroscopic observation of the carboxyl radical confirm its formation as a reaction intermediate. Precise clocking of the lifetimes of radicals generated in situ by an activated C-C bond fission will pave the way for improving the photocatalytic selectivity and turnover. The spectroscopic tracking of complex, multi-step chemical reactions is challenging due to the dynamic timescales of the elementary steps. Here, the authors track a four-step, light-induced decarboxylation reaction in real time to provide new mechanistic insights.